Comparison of the diagnostic performance of the 2017 ACR TI-RADS guideline to the Kwak guideline in children with thyroid nodules. - Shapira-Zaltsberg, Gali; Miller, Elka; Martinez-Rios, Claudia; Bass, Juan; Goldbloom, Ellen B.; Tang, Ken; Hayawi, Lamia; Highmore, Kerri (Pediatric Radiology, 2019)
Background: The Kwak Thyroid Imaging Reporting and Data System (Kwak-TI-RADS) guideline (2011) and American College of Radiology Thyroid Imaging Reporting and Data System (ACR TI-RADS) guideline (2017) were developed as ultrasound (US) risk stratification tools for detecting thyroid malignancy in adults.Objective: The purpose of this study was to investigate the inter-rater reliability and diagnostic performance of the ACR TI-RADS guideline in the pediatric population and compare it to the Kwak guideline.Materials and Methods: This retrospective study comprised 75 children who underwent thyroid US at a tertiary-level pediatric hospital. Three pediatric radiologists and one pediatric radiology fellow graded the US findings using the Kwak-TI-RADS and ACR TI-RADS guidelines. We assessed reliability of radiologists' ratings using percentage inter-rater agreement, and intra-class correlation coefficients (ICC2,1). We assessed area-under-the-receiver-operating-characteristic curve (AUROCC) to compare the discriminative diagnostic ability of the Kwak-TI-RADS and ACR TI-RADS scoring systems against histopathology/cytology, or stability on US over a 2-year follow-up period for cases without tissue diagnosis.Results: The inter-rater agreement was significantly better for the ACR TI-RADS level compared to the Kwak-TI-RADS level (P<0.001) using the percentage pairwise agreement. The ROC curves for assessing the diagnostic performance of the two methods showed no significant difference between the methods. The AUROCCs for the Kwak-TI-RADS and ACR TI-RADS levels were 0.74 (95% confidence interval [CI] 0.67-0.82) and 0.72 (95% CI 0.61-0.82), respectively.Conclusion: Both the Kwak-TI-RADS and ACR TI-RADS guidelines provide moderate malignancy risk stratification for thyroid nodules in the pediatric population, with better inter-rater agreement for the ACR TI-RADS guideline. Further work to adjust the recommendations for pediatric patients is necessary.